Non-coding RNAs to regulate cardiomyocyte proliferation: A new trend in therapeutic cardiac regeneration - Qin, Kele; Xie, Xiaohui; Tang, Weijie; Yang, Danni; Peng, Jun; Guo, Jianjun; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases remains the leading cause of death worldwide, especially ischemic heart disease (IHD). It is also classified as incurable because of the irreversible damage it causes to cardiomyocytes. Therefore, rejuvenating myocardial tissue after ischemia is one of the primary research concerns for scientists globally. The mammalian heart grows after an injury during the embryonic or neonatal period, but this ability disappears with increasing age. Previous studies have found that specific non-coding (nc)RNAs play a pivotal role in this process. This review summarizes the research on cardiomyocyte regenerative medicine in recent years and expounds on the biological functions and mechanisms of micro (mi)RNA, long non-coding (lnc)RNA, and circular (circ)RNA in the posttranscriptional regulation of cardiomyocytes. Furthermore, this review also summarizes the roles of ncRNAs in specific species, and lastly, we discuss potential therapeutic strategies for myocardial infarction.